Penerapan Media Wordwall Untuk Meningkatkan Interaktivitas dan Motivasi Belajar Siswa pada Materi My Family - Wulandari Wulandari; Nanda Ramadani; Inri Ani Gultom; Nazwa Al Zahro; Rizki M Nadeak; Santa Situmorang; Siti Misharyani (Lembaga Pengembangan Kinerja Dosen, 2025)
The English language learning process at SDN 064037 Medan Tembung faces challenges related to a lack of interactivity and optimal utilization of learning media, particularly in the topic My Family. This research aims to analyze the impact of implementing Wordwall media in enhancing student interactivity, understanding of the material, and learning motivation. This study employs a qualitative approach through methods of observation, interviews, and documentation involving 25 fourth-grade students at SDN 064037. The findings of this study indicate that the application of Wordwall in learning significantly improves student interactivity, material comprehension, and their motivation to learn. The interactive features of Wordwall encourage students to be more active during the learning process, positively influencing their learning outcomes. Based on these findings, it is recommended that teachers utilize more varied learning media, such as Wordwall, to enhance the quality of education in elementary schools.